ANALYSIS OF COMPETITIVE STRATEGIES IN INDUSTRIES OF PERU - Gonzales M., Claudio (2003)
This article shows the competitive strategies stated by Michel Porter to keep and/or widen an enterprise within an industrial sector in a free-competence market. Such an analysis focuses on peruvian reality.